Transcendence in Patrick White: the imagery of the Tree of Man and Voss - Van Niekerk, Timothy (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2003)
This study represents an exploration of White's concept of transcendence in The Tree of Man and Voss by means of a detailed account of some of the key patterns of imagery deployed in these novels. White's imagery is a key mode of expression in his work, not simply manifesting in overarching religious symbols and framing structures but figuring in constantly modulated tropes continuous with the narrative, as well as in minor, but no less significant images occasionally susceptible to etymological or onomastic reading. While no attempt is made to provide an exhaustive exploration of the tropes at work in these novels, a sufficient range of material is covered, and its metaphoric density adequately penetrated, to highlight and explore a fundamental concern in White's work with a paradoxical unity underlying the dualities inherent in temporal existence. A useful way of approaching his fiction is to view the perpetual modulations of his imagery as the dramatisation of an enantiodromia or play of opposites, in which the conflicts of duality are elaborated and paradoxically - though typically only momentarily - resolved. This resolution or coincidence of opposites is a significant feature of his notion of transcendence as well as his depictions of illuminatory experience, and in this respect White's metaphysics share an essential characteristic, not only of Christianity, but a range of religious and mythological systems concerned with expressing a transcendent reality. Despite these analogies, however, the novels at hand are not so tightly bound to Christian, or any other, meaning-making systems so as to constitute sustained allegories, and hence this study does not aim to chart a series of correspondences between White's images and biblical or mythological symbols. Indeed, a criticism often levelled at White - with The Tree of Man and Voss typically figuring in support of this claim - is that he too rigidly imposes religious frameworks on his work. An extension of this view is formulated in the Jungian critique of White's corpus offered by David Tacey, who argues that White's conception of transcendence is consistently challenged by the archetypal significance of the images he employs, which point to a contrary process of psycho-spiritual regression in his protagonists. In a fundamentally text-based approach, this study explores White's use of imagery while taking biblical resonances and archetypal interpretations into account, and suggests that, though White's images are highly allusive, they are not merely agents of imported Christian, or other traditional symbolic values. Nor do they undermine the authenticity of his depiction of the spirituality of his protagonists, or obtrude on the fabric of the narrative. Instead, the range of his images are - though often ambivalent - integral to a network of mercurial tropes which articulate and constantly evaluate a notion of transcendence through inflections and oscillations rather than equations of meaning.
Keywords: White, Patrick, 1912-1990. Tree of man; White, Patrick, 1912-1990. Voss